MODEL OF JOB MOTIVATION, COMPENSATION AND CAREER DEVELOPMENT ON JOB SATISFACTION OF EMPLOYEES AT SAHID SUDIRMAN RESIDENCE APARTMENT - Amalia, Lia; Mardiansyah, Ryan (Universitas Pelita Harapan, 2022)
This study aims to examine the Effect Of Work Motivation, Compensation and Career Development on Job Satisfaction of Employees at Sahid Sudirman Residence Apartment. The data used in this study is primary data using questionnaire data from 175 respondents of employees of the Sahid Sudirman Residence apartment. The data is then processed by multiple linear regression method. The results of this study prove that work motivation has a significant positive effect on employee job satisfaction, compensation has a significant positive effect on employee satisfaction, career development has a significant positive effect on employee satisfaction, and Work Motivation, Compensation and Career Development together have a significant effect on job satisfaction.